The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.9734/jgeesi/2020/v24i230199
|View full text |Cite
|
Sign up to set email alerts
|

Chemtrails are Not Contrails: Radiometric Evidence

Abstract: Aims: Concerted efforts are made to deceive the public into falsely believing the jet-emplaced tropospheric aerosol trails, called chemtrails by some, are harmless ice-crystal contrails from aircraft engine exhaust-moisture. Our objective is to use radiometric measurements in the range 250-300 nm to show that a typical chemtrail is not a contrail, and to generalize that finding with additional data.  Methods: We utilized International Light Technologies ILT950UV Spectral Radiometer mounted on a Meade LXD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Scientific publications that do not acknowledge the existence of the use of solar geoengineering by SAI nevertheless shows that persistent aircraft trails are composed of many metal particles [13]. Using solar spectrometry irradiance measurements, a study showed that these persistent aircraft trails are not ice crystal condensation trails, but chemical trails [85]. Documents linking these persistent trails to chemical spray weather modification technology show that the content appears to be particularly concentrated in aluminum (Al), barium (Ba), nanoparticles and sulfur [13].…”
Section: Solar Geoengineering By Saimentioning
confidence: 99%
“…Scientific publications that do not acknowledge the existence of the use of solar geoengineering by SAI nevertheless shows that persistent aircraft trails are composed of many metal particles [13]. Using solar spectrometry irradiance measurements, a study showed that these persistent aircraft trails are not ice crystal condensation trails, but chemical trails [85]. Documents linking these persistent trails to chemical spray weather modification technology show that the content appears to be particularly concentrated in aluminum (Al), barium (Ba), nanoparticles and sulfur [13].…”
Section: Solar Geoengineering By Saimentioning
confidence: 99%
“…Disinformation claiming that the particulate trails represent harmless ice-crystal "contrails" stands in conflict with direct observation, and is disputed by scientific evidence [64]. Aircraft contrails form only briefly in cold, humid atmospheric conditions, unlike the particulate trails that spread out into cirrus-type clouds or even a white haze [65].…”
Section: Horrors Of Tropospheric Aerosol Geoengineringmentioning
confidence: 99%
“…Therefore, to estimate the instrument uncertainty, the smallest division is multiplied by interpolation factor of 0.5 as in Eq. (6).…”
Section: Uncertainty Estimationmentioning
confidence: 99%
“…Instrument uncertainty, a = 0.5 × 0.001 (6) Therefore, the instrument uncertainty for the UV254SD was ± 0.0005. This was taken as a uniformly distributed uncertainty.…”
Section: Uncertainty Estimationmentioning
confidence: 99%
See 1 more Smart Citation